1997
DOI: 10.1038/sj.onc.1201351
|View full text |Cite
|
Sign up to set email alerts
|

Induced direct binding of the adapter protein Nck to the GTPase-activating protein-associated protein p62 by epidermal growth factor

Abstract: The SH3-SH3-SH3-SH2 adapter protein Nck links receptor tyrosine kinases, such as EGF and PDGF receptors, to downstream signaling pathways, among which p21 cdc42/rac -activated kinase cascade, Sos-activated Ras signaling and the human Wiskott-Aldrich Syndrome protein (WASp)-mediated actin cytoskeleton changes, have been implicated. In EGF stimulated cells, Nck coimmunoprecipitates with a number of phosphotyrosine proteins including the EGF receptor (Li et al., 1992 Mol. Cell. Biol. 12: 5824 ± 2833). To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…Tyrosine phosphorylated Dok can then interact with rasGAP. Additionally, Dok was also phosphorylated upon stimulation of the EphB2 receptor (Holland et al, 1997) and the EGF receptor (Tang et al, 1997) and in both instances, phosphorylated Dok was associated with Nck. Taken together, this suggests that upon tyrosine phosphorylation, Dok and Dok-R may interact with a similar repertoire of downstream substrates.…”
Section: Discussionmentioning
confidence: 95%
“…Tyrosine phosphorylated Dok can then interact with rasGAP. Additionally, Dok was also phosphorylated upon stimulation of the EphB2 receptor (Holland et al, 1997) and the EGF receptor (Tang et al, 1997) and in both instances, phosphorylated Dok was associated with Nck. Taken together, this suggests that upon tyrosine phosphorylation, Dok and Dok-R may interact with a similar repertoire of downstream substrates.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, several tyrosine phosphorylation sites are present creating docking sites for Src homology 2 (SH2) domain-containing adapter molecules such as Nck, the Ras GTPase-activating protein (RasGAP) or the product of the X-lymphoproliferative syndrome gene, SH2D1A/SAP. 3,[6][7][8] The structure of Dok-1 presents some similarities with other adapter molecules such as Gab proteins or insulin receptor substrate (IRS) proteins. 9,10 Two proteins sharing extensive sequence homology with the amino-terminal part (PH and PTB domains) of Dok-1 have been cloned: Dok-2 (also known as FRIP or Dok-R) [11][12][13][14] and Dok-3 (also known as Dok-L).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nck binds directly to the ligand-stimulated PDGF receptor-␤ . On the other hand, Nck appears to associate with the activated EGF receptor indirectly via the GTPase-activating protein (GAP)-associated phosphotyrosine protein p62 (Tang et al, 1997). Studies using monoclonal anti-phospholipase C-␥1 antibodies have shown that Nck shares a common epitope with phospholipase C-␥1 (Park and Rhee, 1992;Meisenhelder and Hunter, 1992), and a mouse Nck cDNA has been isolated using an anti-phospholipase C-␥1 monoclonal antibody (Park, 1997).…”
Section: Introductionmentioning
confidence: 99%